2019
DOI: 10.1016/j.radcr.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute gouty arthritis following percutaneous cryoablation of renal cell carcinoma

Abstract: We report a case of acute gouty monoarthritis of the left ankle in a 58-year-old female with chronic renal insufficiency after cryoablation of a 3.8 cm left renal cell carcinoma. The patient's symptoms resolved after intravenous Solumedrol and did not recur at her 1-month follow-up visit. To the best of our knowledge, this is the first reported case of acute gouty monoarthritis after cryoablation of a renal cell carcinoma lesion in a patient with underlying chronic renal insufficiency. Clinicians should be vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…With the prophylactic medications consisting of allopurinol 100 mg and colchicine 0.6 mg daily during the whole period of gemcitabine chemotherapy could prevent GA attack. Mohamed et al [10] reported a case of acute gouty monoarthritis of the left ankle in a 58-year-old female with chronic renal insufficiency. After the cryoablation of a 3.8 cm left renal cell carcinoma, the patient's symptoms disappeared after intravenous Solumedrol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the prophylactic medications consisting of allopurinol 100 mg and colchicine 0.6 mg daily during the whole period of gemcitabine chemotherapy could prevent GA attack. Mohamed et al [10] reported a case of acute gouty monoarthritis of the left ankle in a 58-year-old female with chronic renal insufficiency. After the cryoablation of a 3.8 cm left renal cell carcinoma, the patient's symptoms disappeared after intravenous Solumedrol.…”
Section: Discussionmentioning
confidence: 99%
“…According to the available literature [10][11][12][13][14][15][16][17][18][19], gouty arthritis usually occurs in patients with hyperuricemia and it can be induced by a variety of factors. Here, we describe a case of acute gouty arthritis attacks caused by a great toe injury, which was successfully treated with benzbromarone and ibuprofen.…”
Section: Introductionmentioning
confidence: 99%